Pyelonephritis in Pregnancy: Clinical and Laboratorial Aspects and Perinatal Results - Djulie Anne de Lemos Zanatta; Mariane de Mello Rossini; Alberto Trapani Júnior (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2017)
Abstract Objective To identify the prevalence of pyelonephritis during pregnancy and to analyze the clinical and laboratorial aspects, perinatal results and complications. Methods A transversal study of 203 pregnant women who had pyelonephritis during pregnancy and whose labor took place between 2010 and 2016 at a hospital in the state of Santa Catarina, Brazil. The analysis was based on medical records as well as on the hospital's database. Clinical and laboratory conditions, antibiotics, bacterial resistance, perinatal outcomes and complications were all taken into account. The data was compared using the Mann-Whitney test and the Chi-square test. Results A prevalence of 1.97% with pyelonephritis was evidenced, with most patients having it during the second trimester of gestation. The bacteriamost commonly found in the urine cultures was Escherichia coli, in 76.6% of cases, followed by Klebsiella pneumoniae (8.7%). Ceftriaxone had the lowest bacterial resistance (only 3.5% of the cases). On the other hand, ampicillin and cephalothin presented higher bacterial resistance, 52% and 36.2%, respectively. The risk of very premature delivery was more than 50% higher in patients with pyelonephritis. Conclusion Ampicillin and first-generation cephalosporins are associated with a higher bacterial resistance while ceftriaxone proved to have a high efficacy for the treatment of pyelonephritis due to low bacterial resistance. Patients with pyelonephritis showed a higher risk for very premature delivery (< 32 weeks). In this casuistry, there were no others significant differences in the overall perinatal outcomes when compared with the routine service series.